O papel dos processos fluviais na evolução do modelado do relevo na bacia do Rio Paraúna, Serra do Espinhaço Meridional - MG - Alex de Carvalho (2019)
The Southern Espinhaço Range is one of the major geological and geomorphological domains in Minas Gerais state. The greater part of this domain is drained by the Paraúna River basin. Academic literature shows however that geomorphological works have prioritized the physiographic unit of Gouveia Depression, a compartment of the Southern Espinhaço Range drained by the Chiqueiro River basin, one of the main tributaries of Paraúna River. Despite the Range’s significance, holistic research approaches are rare on fluvial geomorphology of the main valleys of Paraúna’s tributaries, leaving room for new studies that seek to advance the comprehension regarding the relationship between geomorphological setting and fluvial systems in this basin. Considering this matter, this thesis aims to discuss quaternary geomorphological evolution (Upper Pleistocene and Holocene) in Southern Espinhaço Range, particularly focusing on the roles of fluvial processes in landscape configuration in Paraúna River basin. The research is based on Fluvial Geomorphology knowledge and seeks to investigate regional morphogenesis considering the interpretation of terraces and fluvial depositional sequences. The study followed: i) systematization of data and information on Espinhaço Range and Gouveia Depression; ii) identification, characterization and mapping of terraces and fluvial depositional sequences; iii) dating of sediments through Optically Stimulated Luminescence (OSL); and iv) morphometrical analysis of river basins and drainage network. Valley bottoms with three depositional levels are predominant, usually embedded or with gentle incision, that indicate to regional and/or local base level stability. There are four strath terraces on a slope, suggesting base level (regional or local) oscillation during Upper Pleistocene and Early Holocene. The dated sediments present ages that vary from 170 ± 25 years to 26.350 ± 4.470 years, allowing the proposition of a chronological setting of Pleistocenic and Holocenic paleoenvironmental sceneries for the Paraúna River basin that together with the spatial distribution of depositional levels has allowed us to discuss the influence of base level oscillation and climatic conditions in erosive-depositional dynamics. Neotectonic control in fluvial evolution, favored by the regional structural setting is responsible for a differential dynamic in uplifted and tilted blocks, evidenced by depositional levels, drainage structure, fluvial features and morphometric parameters. The holistic analysis of depositional levels’ attributes and proposed paleoenvironmental sceneries as well as morphometric analysis it was concluded that the fluvial and geomorphological evolution of the depressed compartment is characterized by: (i) lithostructural control and the elevation/tilted of the elevated east and west sectors, whose signs are drainage anomalies, with eastward channel displacement and predominantly deposited depositional levels , in the right margin of the channels; (ii) the transitional relief on the rocks of the Gouveia Complex, in which the active gullies would be responses to the destabilization of the slopes, from the last lowering of the base level; (iii) by the current stabilization of the regional base level, represented by the Paraúna river, which conditions the regularization of longitudinal profiles of the channels and the consequent reduction of energy in the regularized segments, intensifying the reinforcement of bed armouring; and (iv) the lateral retreat of the cliffs in the contact between the Gouveia Depression and the West Bank Blocks of the Paraúna River basin, responsible for the expansion of the Depression.